Cultures of Shame - Nash, D. author. aut Link
IX, 244 p.
Keywords: The first systematic study of the concept of shame from 1600-1900, showing good and bad behaviour, morality and perceptions of crime in British society at large. Single episodes in the history of shame are contextualized by discussing the historiography and theory of shame and their implications for the history of crime and social relations.